1969
DOI: 10.1161/01.cir.39.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Baroreflex Sensitivity in High Blood Pressure

Abstract: Sudden intravenous injections of small amounts of angiotensin or phenylephrine were given to 30 subjects to produce modest, brief increases in directly measured systemic arterial pressure. A plot of each systolic pressure against the second succeeding cardiac cycle length produced a linear distribution, the slope of which was expressed as the millisecond increase in cycle length per mm Hg rise in systolic pressure. The slope is an index of baroreflex sensitivity and was found to have an average value of 12.8 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
269
3
9

Year Published

1970
1970
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 550 publications
(293 citation statements)
references
References 25 publications
12
269
3
9
Order By: Relevance
“…Importantly, evidence now accumulating suggests that impaired BRS may precede development of hypertension [40][41][42]. We have previously demonstrated that even in the absence of diabetic kidney disease, type 1 diabetes is associated with isolated systolic hypertension and a prematurely increasing pulse pressure, suggestive of accelerated arterial stiffening [43].…”
Section: Discussionmentioning
confidence: 91%
“…Importantly, evidence now accumulating suggests that impaired BRS may precede development of hypertension [40][41][42]. We have previously demonstrated that even in the absence of diabetic kidney disease, type 1 diabetes is associated with isolated systolic hypertension and a prematurely increasing pulse pressure, suggestive of accelerated arterial stiffening [43].…”
Section: Discussionmentioning
confidence: 91%
“…Recent evidence suggests that changes in arterial baroreflex control and the autonomous nervous system are involved in the development and maintenance of hypertension. [29][30][31] In a classic study carried out in the 1960's, Bristow et al 32 reported for the first time that the baroreflex control of HR in patients with hypertension was significantly lower than that of normotensive individuals. Herein, we have observed that baroreflex sensitivity in normotensive rats is much higher than in SHRs, which supports the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Systolic BP instead of MAP was used in the calculation because of the ease and accuracy of this measurement. 25 …”
Section: Carotid Baroreceptor Sensitivitymentioning
confidence: 99%